STRATEGI KOMUNIKASI PEMASARAN TEH TONG TJI MELALUI INSTAGRAM DALAM MEMBANGUN BRAND RECOGNITION - Anandianskha, Sawaviyya; Harahap , Halomoan (Program Studi Ilmu Komunikasi Universitas Paramadina, 2025)
Digital transformation has reshaped marketing practices, with Instagram emerging as a key platform for building brand recognition. This study examines the marketing communication strategy of Teh Tong Tji on Instagram, emphasizing the use of Reels, Stories, and visual elements to enhance audience engagement. A qualitative approach, guided by Social Media Engagement Theory (SME), was employed through in-depth interviews, content observation, and document analysis. Findings reveal that audience engagement remains limited due to inconsistencies in delivering relevant and appealing content. Among the available features, Reels and Stories proved most effective in generating higher interaction rates, including likes, comments, and shares. Visual storytelling, particularly product introduction videos, was found to play a significant role in strengthening brand recognition. Thematic analysis further highlights the necessity of aligning content strategies with audience preferences, as well as the importance of ongoing evaluation to optimize algorithm performance. This study contributes to the digital marketing literature by offering insights into how traditional brands can adapt their communication strategies to remain competitive in the social media era. Practical recommendations include enhancing content consistency, leveraging interactive features, and refining visual elements to better meet audience needs and foster stronger brand recognition.